A sustainable approach to synchronous improvement of wet-stability and toughness of chitosan films. (February 2022) - Mu, Bingnan; Wu, Qianmei; Xu, Lan; Yang, Yiqi
Abstract: Wet-stability and toughness of chitosan films were improved synchronously via the establishment of formyl-saccharide intermolecular bonds. Poor wet stability and inferior mechanical properties limit the large-scale application of chitosan films. Previous crosslinkings using saccharide-aldehydes caused concerns such as formaldehyde, weakened mechanical properties, and changed cytocompatibility. Here we developed formaldehyde-free formyl-saccharides via control of oxidation conditions. Mechanical properties of chitosan products could be improved using different structures of formyl-saccharides with minimal amounts. With only 0.5% of sucrose-aldehydes(SU3) and raffinose-aldehydes(RA4), breaking strength and strain of chitosan films increased from 28 to 38 MPa and from 19% to 48%, respectively. Further increase in concentrations of crosslinkers contributed to more improvement of properties of chitosan films. Chitosan films with 2% of sucrose-aldehydes (SU3) had an increase in wet strength from 0 to 14 MPa and almost 100% weight retention in acidic water. Crosslinkages of formyl-saccharides did not change cytocompatibility and color of films. Graphical abstract: Image 1 Highlights: Chitosan films with desirable wet stability and toughness were developed. Minimal formaldehyde-free formyl-saccharides ameliorated film properties. Cytocompatibility of films was not altered by formyl-saccharides. Length of crosslinkages controlled properties of chitosan products. This work potentially realizes industrialized applications of chitosan films.